Creative Marketing Strategies in Building the Brand Image of Value-Based Educational Institutions - Ariska Dwi Oktaria; Grace Theo Fany Dagambir; Peter Julio Tarigan; Yohanes Budi Sarwoko (Pustaka Digital Indonesia, 2026)
This study analyzes the role of creative marketing strategies in building the brand image of value-based educational institutions. Specifically, it examines digital creative execution, customer retention strategies, and the mediating role of consumer insight alignment. The research employed a qualitative case study approach conducted at Labs School Kaizen, a value-based educational institution in Indonesia. Data were collected through in-depth interviews with 15 informants consisting of management, marketing staff, and parents. This was complemented by digital activity observation and documentation analysis of 124 social media posts over a six-month period. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing/verification. The findings reveal that value-based positioning emerges as the dominant strategy in differentiating the institution through the integration of spiritual and academic values. Digital creative execution is reflected in student storytelling content, parenting education content, and parent testimonials, which collectively enhance emotional engagement and institutional credibility. Furthermore, customer retention strategies implemented through relational communication, parenting webinars, and parent communities significantly strengthen trust, loyalty, and word-of-mouth advocacy. The study also demonstrates that consumer insight alignment particularly parents’ concerns about moral degradation and their aspirations for academic–spiritual integration plays a crucial mediating role in reinforcing the relationship between creative marketing strategies and brand image formation. This study contributes to the literature by extending existing marketing communication theories to incorporate a values-driven perspective in educational branding. Practically, the findings advise educational managers to prioritize parenting education content and parent-community building as core branding tools, shifting from transactional promotions to trust-based relationship management.